Developing Role Playing Games for the Skill of Reading the Arabic Language - Farhan, Ali; Kamal, Muhammad; Sarip, Mohamad (Institut Agama Islam Negeri Curup, 2024)
This research aims to develop Arabic reading skills learning media based on Role Playing Games. This research discusses efforts to increase interest and motivation in reading and understanding Arabic texts among students. This study applies the ADDIE model in the development of Role Playing Games-based learning media in MAN 1 Bogor in the Gaza semester of the 2023/2024 academic year. The Media Role Playing Games developed have been validated by media, language, and material experts. The validation results showed that this medium was very good, with a percentage of 97% of media experts, 86% of linguists, and 98% of material experts. In addition, the response from teachers also showed positive results with a percentage of 95%. User tests of students also gave satisfactory results, with one-on-one tests obtaining 86%, small group tests 94%, and large group tests 89%. Based on the results of validation and user tests, it can be concluded that the learning media of Arabic reading skills based on Role Playing Games is very feasible to use for grade XI MAN students. In addition, student responses show that this Arabic-based Role Playing Games media is interesting, easy to use, and can be accessed and played for free on smartphones.